Relações entre apreciação estética e o uso de sequências didáticas no processo de alfabetização e formação da criança leitora - Oliveira, Júlia Emanuelly de (2017)
This research was developed within the Master Degree Program in Education of the Federal University of Mato Grosso, in Rondonópolis city (PPGEdu/UFMT/CUR), in the line of research Languages, culture and knowledge construction process: historical and contemporary perspectives. It was constructed based on the discussions proposed within the research group Scholar Literacy (ALFALE). This Masters’ thesis is an investigation about the aesthetic appreciation of literary work and its usage in didactic sequences in the early years of elementary school. Thus, the research intends to discuss how does teachers suggest the literary work usage in didactic sequences. We analyzed didactic sequences elaborated by teachers who participated of the teachers training program National Pact for Literacy at the Right Age, in Mato Grosso State. The material was collected through a preliminary analysis of the closing seminars’ annals of the National Pact for Literacy at the Right Age’s courses (considering the years of 2013, 2014 and 2015). We analyzed one thousand thirteen (1.013) study guidelines’ abstracts containing teachers’ experience reports of the work developed based on their didactic sequences. Fifty-three (53) abstracts were selected considering the research’s purposes. These abstracts mentioned the work developed by teachers and/or proposed didactic sequences and also mentioned the inclusion of literary work. The following step was to establish contact with the authors through email or telephone. Fifteen (15) teachers answered our calls. They sent us some documents in response (the didactic sequences developed and other proposals not necessarily done in classroom and other materials). We analyzed the data provided by these materials categorizing and interpreting them. This investigation is based on Content Analysis sustained by the methodological referential of Bardin (2002), Bakhtin (2011), Coelho (2002), Cosson (2006), Cunha (1994), Schneuwly; Dolz (2004), Zabala (1998), Zilberman (2003) among other authors who also discuss the aesthetic appreciation of literary work and the concept of didactic sequences. Thereby, this investigation aims to inspire educators and writers to reflect about children’s literature, considering it as a cultural, historical and social knowledge source and assuming its contributions for children's development and their knowledge expansion.